New epidemic of malnutrition in young Slovenian athletes - Peklaj, Eva (Zdravstveno varstvo, 2023)
Objective: The syndrome of relative energy deficiency in sports (RED-S) is the result of a prolonged period of low energy availability in athletes and leads to the deterioration of health and physical performance. Our study aimed to investigate the prevalence of RED-S-related health and performance problems in young Slovenian athletes, comparing middle (14-17 years) with late (18-21 years) adolescents. Methods: We analysd data of 118 young athletes (61 females, 57 males) who had nutritional assessments. Statistical analysis was carried out to determine the prevalence of RED-S-related problems. RED-S was diagnosed using the Relative Energy Deficiency Tool and the Sports Clinical Assessment Tool. Nutrition-related risk factors for RED-S were assessed with the use of a questionnaire and analysis of a three-day food diary. Results: The majority of athletes had at least one RED-S-related health disorder. The number of health-related disorders was significantly higher in females 3.0 (0.2) compared to males 1.6 (0.2). It was also significantly higher in middle 2.6 (0.2) compared to 1.9 (0.3) late adolescents. Potential nutritional risk factors for RED-S were low carbohydrate intake, skipping meals before and after practice, a desire to lose weight, and a history of weight loss in the past year. Conclusion: The prevalence of health-related RED-S disorders and performance problems in young athletes is concerning, and our study indicates that middle adolescents are more vulnerable to this than late adolescents. Our findings suggest that screening for RED-S symptoms and nutrition-related risk factors for RED-S should be included in regular medical examination of young athletes.
Keywords: low energy availability; mladi športniki; nizka energijska razpoložljivost; nutritional risk; prehransko tveganje; relative energy deficiency in sport; sindrom relativnega energijskega pomanjkanja v športu; young athletes